Investigating the Effect of Internal Marketing Strategy and Environmental Factors on Performance Mediated by Internal Processes at Al-Qadisiyah University in Iraq - Poursalimi, Mojtaba; Rahimnia, Fariborz; Al-Ramahi, Nadia Kazem Awad (جامعة القادسية - كلية الادارة والاقتصاد, 2021)
The aim of this study was to investigate the effect of internal marketing strategy, competitive strategies and environmental factors on performance mediated by internal processes at Al-Qadisiyah University in Iraq. This research is applied in terms of purpose and is survey-analytical in terms of method. Simple random sampling was used and 303 managers and employees were assessed. To assess the internal process, the questionnaire of Salehzadeh et al. Was used. The Mooney and Froman questionnaire, Porter’s competitive strategies, Wang et al.’s environmental factors, and Zandi’s performance were used to measure internal marketing. Then the relationship between the variables was analyzed by structural equation method and pls smart software. Finally, the results showed that internal marketing strategy, competitive strategies and environmental factors have a positive and significant effect on performance mediated by internal processes at Al-Qadisiyah University in Iraq.
Keywords: التسويق الداخلي -- القدرة التنافسية -- التميز المؤسسي -- مؤسسات التعليم العالي -- العراق